Integrative taxonomy of Coriophagus bulbosus sp. nov. (Strepsiptera: Halictophagidae) with a tentative phylogeny of the species and first report of a stylopised mango leafhopper, Idioscopus nitidulus (Walker, 1870) (Hemiptera: Cicadellidae) from India - Hui, Poulami; Hazra, Niladri (Zootaxa, 2025)
A new species of Coriophagus Kinzelbach (Strepsiptera: Halictophagidae) is herein described from West Bengal, India, raising the total number of Indian representatives of the genus to three. Coriophagus bulbosus sp. nov. is distinguished from its congeners by a combination of unique morphological traits, with its taxonomic status further corroborated through DNA barcoding. A tentative phylogenetic hypothesis for the genus, based on adult male morphology, is provided, alongside a revised global identification key to adult males. Additionally, we report a novel host association: the mango leafhopper Idioscopus nitidulus (Walker, 1870) (Hemiptera: Cicadellidae), found parasitised by C. chaudhuri Hui, Mukherjee & Hazra, 2023.